Imaging in Zinner Syndrome, A Case Series: The Wolf in Sheep’s Clothing - V. Pramod; S.C. Sanjay; S. Tanuj Sai Kumar (Urology Case Reports)
Zinner syndrome is a rare congenital malformation of the Wolffian duct with seminal vesicle cyst, ipsilateral renal agenesis and ejaculatory duct obstruction, seen in less than 0.002 % of the male population. An increased awareness among clinicians, urologists, and radiologists is essential, as early diagnosis and management can impact fertility outcomes. This review aims to explain and illustrate Zinner syndrome through imaging case studies. Emphasis is made on considering Zinner syndrome in the differential diagnosis of young males with pelvic pain and renal agenesis, highlighting the importance of radiological evaluation for the management of this uncommon yet clinically significant condition.